Corticosteroid delivery using oral mucosa equivalents for the treatment of inflammatory mucosal diseases - Zulfahmi Said; Craig Murdoch; Jens Hansen; Lars Siim Madsen; Helen E. Colley (John Wiley & Sons Ltd, 2024)
European Journal of Oral Sciences Volume 129 Issue 5 Page (1-12)